2019
DOI: 10.1111/nmo.13580
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical characterization of the enteric neurons within the porcine jejunum in physiological conditions and under the influence of bisphenol A (BPA)

Abstract: Background Bisphenol A (BPA) is commonly used in the production of plastics and has multidirectional, negative effects on the living organisms. It may also affect the enteric nervous system (ENS) located in the wall of the gastrointestinal tract. Enteric neurons express many active substances, which regulate majority of intestinal activities not only in physiological conditions but also under the impact of pathological factors. Methods The influence of various doses of BPA on the ENS of jejunum has been invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 78 publications
(191 reference statements)
6
15
1
Order By: Relevance
“…The large population of CART-IR neurons in the MP may suggest that this active substance is involved in the regulation of intestinal motility. Other authors have also observed a high number of myenteric CART-positive nerve cells in the porcine small intestine, which is consistent with results obtained in our experiment [23,70]. Possible motor functions of CART were also studied in vitro in rats (stomach, ileum and colon) and a similar dependence was found [69].…”
Section: Discussionsupporting
confidence: 92%
“…The large population of CART-IR neurons in the MP may suggest that this active substance is involved in the regulation of intestinal motility. Other authors have also observed a high number of myenteric CART-positive nerve cells in the porcine small intestine, which is consistent with results obtained in our experiment [23,70]. Possible motor functions of CART were also studied in vitro in rats (stomach, ileum and colon) and a similar dependence was found [69].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, it has been noted that NO acts as a cytoprotective agent during some intestinal injuries and endotoxicities, mainly via the regulation of the mucosal blood flow [ 37 , 38 ]. It has also been reported that the endogenous release of this gaseous neurotransmitter induces protective effects of other active substances in the nervous system within the GI tract [ 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in enteric neurons are a sign of the adaptive and protective reactions and contribute to homeostasis maintenance in the GI tract [ 164 , 165 ]. Moreover, such changes appearing under the impact of disease or toxic substances may be the first signs of subclinical pathological processes or toxicity [ 166 ]. Some studies have indicated that mycotoxins may affect the morphology and neurochemical character of the enteric neurons.…”
Section: Anatomy Of the Enteric Nervous Systemmentioning
confidence: 99%
“…The regulation of intestinal activity through the gut–brain axis is more likely since CART is known as an important factor regulating the feeding behavior in the central nervous system [ 185 ]. Moreover, numerous studies in which an increase in CART levels in the ENS has been observed strongly suggest that this peptide also takes part in protective and adaptive reactions in response to pathological, toxicological and physiological factors [ 46 , 166 , 184 ].…”
Section: Mycotoxins Affecting the Enteric Neuronsmentioning
confidence: 99%